ISSUES OF ADAPTATION AND MITIGATION OF GLOBAL CLIMATE CHANGE IN THE SYSTEM OF THE US DEPARTMENT OF DEFENSE - Elov Ashrafjon (Ecominds Press, 2025)
This article outlines views on climate change and security, the need to combat climate change, regulations adopted by the U.S. Department of Defense to adapt to climate change and mitigate its effects, organizational units and their activities, measures and best practices implemented in the U.S. Armed Forces in this area. In particular, the laws on the authorization of national defense adopted by the US Congress in the period from 2018 to 2024 analyzed the measures that need to be taken taking into account the effects of climate change.
Keywords: USA, Department of Defense, climate change, army, climate impact, adaptation, danger, threat, assessment.